ChemInform Abstract: Nitrogen‐Containing Privileged Structures and Their Solid‐Phase Combinatorial Synthesis. Issue 35 (8th August 2013) - Verma, Amit; Yadav, Mange Ram; Giridhar, Rajani; Prajapati, Navnit; Tripathi, Avinash C.; Saraf, Shailendra K.
Abstract Review: 240 refs.